Analisis Tingkat Literasi Keuangan dan Perilaku Keuangan Terhadap Keputusan Berinvestasi pada Generasi Z (Lembaga Pengembangan Kinerja Dosen, 2025)
This research investigated how financial literacy and financial behavior influence investment decisions among Generation Z, focusing specifically on students at Surabaya State University. We used a quantitative survey approach, gathering data from 270 student participants through questionnaires. The data was then analyzed using a multiple linear regression test with SPSS Version 27. Our findings reveal that both financial literacy and financial behavior have a positive and significant effect on investment decisions. These results underscore the importance of boosting students' financial knowledge and encouraging healthy financial habits, as they are crucial for future investors. Additionally, the study suggests that universities should consider developing more extensive financial education programs.